Free Flow on MHD Convention in the Presence of Radiation Parameter on Heat Source with Vertical Plates - et. al., M. S. Srinivasa Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper discusses the continuous impact of MHD free convection in the presence of radiation on an infinite vertical plate with heat source with reference to all important parameters which occur in field equations. The governing equations are built by the normal approximation of Boussinesq. The dilemma is addressed by means of disruption technologies. The results are obtained for tempo, temperature, amount of Nusselt and skin friction. The impacts of the magnetic parameter, prandtl, Grashof number, permeability parameter, source/sink parameter and radiation parameter are addressed and displayed with graphs and tables.